MODIFIKASI MESIN PENGERING BIJI-BIJIAN DENGAN BAHAN BAKAR TEMPURUNG KELAPA - Asrianto, Asrianto; Jamaluddin, Jamaluddin; Kadirman, Kadirman (Universitas Negeri Makassar, 2018)
This study aims to determine the modification of the drying machine using coconut shell fuel and to determine the fuel requirements during the drying process of grain (rice grain). This research is a design research. The procedure for carrying out this research includes designing tools, making frames, making framework that can be used by thermometers and fans, as well as making furnaces. During the research process the parameters observed were the consumption of fuel used during the drying process. The research data was obtained from the results of the test machine dryer. Data analysis techniques used are descriptive analysis techniques. The results showed that consumption of coconut shell fuel for 4 hours of drying was 13.5 kg. The drying result from wet grain is 18 kg to 16.2 kg dry grain with an average dry water content of 12.76%